Sleep quality in women with nausea and vomiting of pregnancy: a cross-sectional study - Linda Laitinen; Miina Nurmi; Päivi Rautava; Mari Koivisto; Päivi Polo-Kantola (BMC, 2021)
Abstract Background Nausea and vomiting of pregnancy (NVP) deteriorates many aspects of daily lives of women. However, little is known about associations between NVP and sleep quality. Methods Women attending to routine mid-pregnancy visits in maternity health care clinics in Turku city area and surrounding municipalities, Finland, during 2011-2014, were invited to participate. A cohort of 1203 volunteers (mean age 30 years, mean gestational week 16.6, mean BMI 24.4 kg/m2, nulliparous 46%) was recruited. The severity of NVP in the worst 12-h period of current pregnancy was assessed with Pregnancy Unique Quantification of Emesis Questionnaire (PUQE) and categorized accordingly into no/mild/moderate and severe NVP. Sleep disturbances during the past 3 months were assessed with selected questions (difficulty falling asleep, night awakenings, too early morning awakenings and sleepiness during the day) from Basic Nordic Sleep Questionnaire (BNSQ). In addition, general sleep quality, as well as physical and mental quality of life (QoL) were rated with three visual analog scales (VAS). Associations between PUQE categories (severity of NVP) and sleep disturbances, general sleep quality, physical QoL and mental QoL were evaluated with multinomial regression analysis. Results According to PUQE, NVP was most frequently moderate (n = 629, 52.3%), followed by mild (n = 361, 30.0%) and severe (n = 77, 6.4%). Only 11.3% had no NVP (n = 136). The most frequent sleep disturbance was night awakenings (69.9%, n = 837), followed by sleepiness during the day (35.7%, n = 427), too early morning awakenings (12.0%, n = 143) and difficulty falling asleep (7.1%, n = 81). In adjusted analysis (age, parity, body mass index, smoking, employment), more severe NVP was associated with night awakenings (AOR 3.9, 95% CI 1.79-8.47, P < 0.0001) and sleepiness during the day (AOR 4.7, 95% CI 2.20-9.94, P < 0.0001). In VAS, women with more severe NVP rated worse general sleep quality and worse physical and mental QoL. However, in multivariable analysis, the association between the severity of NVP and physical and mental QoL was stronger than that of sleep . Conclusions More severe NVP is associated with sleep disturbances and in close relation to lower physical and mental QoL. Thus, in comprehensive care of women with NVP, also sleep quality should be evaluated.